DISCOURSE ANALYSIS OF DECENTRALIZATION POLICY MAKING PROCESS OF PROTECTED FOREST MANAGEMENT - Sulistya Ekawati; Hariadi Kartodihardjo; Dodik Ridho Nurrochmat; Hardjanto -; Hariyatno Dwiprabowo (Indonesian Journal of Forestry Research, 2013)
”Decentralization of protected forest management from central to district government has not yet been implemented effectively. This effectiveness depends on many factors that include policy contents and political process or discourse in the policy making process. This study aimsto: 1) analyze the discourse in policy making process of decentralization in the management of protected forests, 2) analyze the actors/networks and their interests and 3) find out policy space for future policy reform. Both quantitative and qualitative approaches were used in the study. The results show that there are three discourses in the policy-making process of decentralized management of protected forests, namely: i) democratic discourse (with story line of externality and accountability, supported by an association forum of Indonesian district government and  decentralization experts); ii) economic discourse (with story line of efficiency, supported by businessmen, Association of Indonesian Provincial Government and World Bank); and iii) democratic and economic discourses. The House of Representatives (DPR) and Ministry of Home Affairs have authorities and capacities to integrate two discourses. Redefining of externality and interdependency can be used as narratives of new policies to improve the policy of decentralized protected forest management.